Improving ischaemic skin revascularisation by nerve growth factor in a child with crush syndrome. Issue 5 (1st November 2002) - Chiaretti, A; Piastra, M; Caresta, E; Nanni, L; Aloe, L
Abstract : Nerve growth factor (NGF) is the first described neurotrophin that stimulates the growth and differentiation of nerve cells and promotes skin and peripheral tissue regeneration. Recent studies suggest that NGF influences endothelial cell proliferation and angiogenic activity. In view of these proposed regenerative effects, we evaluated the efficacy of subcutaneous administration of highly purified murine NGF in a child with severe crush syndrome of the lower left limb. NGF 10 μg was administered subcutaneously every eight hours for seven days to the extensive ischaemic skin lesion of the calcaneal area. After treatment we observed gradual improvement of the ischaemic area; no side effects were noted. The child was discharged in good clinical condition to await a limited calcaneal escharotomy.